Globalisasi: Pernikahan Transnasional di Kepulauan Riau - Nadasyifa Vraba Santi (Journal of International Relations, 2023)
ABSTRACTTransnational marriage is a marriage that occurs between Indonesian Citizens and Foreign Citizens, this phenomenon arises because of globalization. Transnational marriages occur in the Riau Archipelago, an island directly adjacent to Malaysia and Singapore. This study aims to explain the process and the impact of globalization in transnational marriage in the Riau Archipelago with the concept of Globalization: Connectivity, Mobility, and Migration. This research uses qualitative methods with data obtained from literature studies from journals, books, newspapers, and related sites; field studies in the Riau Archipelago. The research was conducted from 2015 to 2021. This research shows that Globalization make a development in Transnational Marriage in the Riau Archipelago.Keywords: Transnational Marriage, Riau Archipelago, Globalization